Tetracycline resistance mediated by tet efflux pumps in clinical isolates of Acinetobacter baumannii - Beheshti, Maryam (2020)
Acinetobacter baumannii is one of the most frequent nosocomial pathogen capable of acquiring resistance to different antimicrobials. The aim of this study was to investigate the activity of tetracycline, doxycycline and minocycline, the prevalence of tet(A) and tet(B) determinants, and the role of efflux pump in tetracycline resistance among the A. baumannii clinical isolates. Susceptibility of 98 A. baumannii isolates to tetracyclines was evaluated by disk diffusion method. The presence of active efflux pump was investigated by determination of the minimum inhibitory concentration (MIC) of tetracycline using the carbonyl cyanide 3-chlorophenylhydrazone (CCCP). Polymerase chain reaction (PCR) was performed to investigate the presence of tet(A) and tet(B) determinants in tetracycline-resistant isolates. The rate of resistance to tetracycline, doxycycline and minocycline was 47.95%, 0%, and 30.61%, respectively. Among the 47 tetracycline-resistant isolates, 29.79% were originated from burned patients and showed MIC ranging from 128-256 µg/mL with both MIC50 and MIC90 values of 256 µg/mL, while 70.21% were from ventilator-associated pneumonia (VAP) patients and had MIC values ranging from 32-1024 µg/mL, with MIC50 and MIC90 of 512 µg/mL and 1024 µg/mL, respectively. The tet(B) gene was found in 61.7% of tetracycline-resistant isolates, while none of the isolates carried the tet(A) gene. CCCP led to 2-128-fold reduction in tetracycline MIC of the tested isolates. The results showed that doxycycline and minocycline are promising agents for the treatment of A. baumannii infections. This study has also revealed the role of efflux activity in the resistance to tetracycline of A. baumannii isolates. The emergence of resistance to these agents is likely due to the spread of clones presenting with a higher prevalence of resistance determinants.